Multifaceted perception of school climate: association between students’ and teachers’ perceptions and other teacher factors - Hirata, Ikue; Nishimura, Tomoko; Osuka, Yuko; Wakuta, Manabu; Tsukui, Nobuaki; Tsuchiya, Kenji J.; Senju, Atsushi (Frontiers in Education, 2024)
This study aimed to investigate whether there is a significant association between teachers’ and students’ perceptions of school climate, and if not, whether teacher factors are associated with the respective perceptions. The participants included 1,831 students and 59 homeroom teachers from 11 public elementary and junior high schools in Japan. Multilevel models were used to examine the association between students’ and teachers’ perceptions of school climate. Results show that, of the three teacher-rated school climate scales, only teacher-perceived disciplinary climate was associated with students’ perceptions of school climate. Teachers’ working conditions, such as self-efficacy and stress, were associated with teachers’ perceptions but not students’ perceptions of school climate. Disciplinary climate was associated with students’ perceptions of school climate, even after accounting for the teachers’ working conditions. Items questioning specific student behaviors, such as those included in the disciplinary climate scale, may be effective in avoiding incongruence with student evaluations. Moreover, maintaining disciplinary climate itself is important for students’ positive perceptions of the school climate. A disciplinary climate in which teachers and students share responsibility for learning and classroom organization, and strategies that support positive student behavior are preferable to exclusionary discipline strategies. Incorporating feedback data gathered through classroom observations or student perceptions is also important in resolving the incongruence between teachers’ and students’ perceptions of the school climate.